Suppression of ribosomal reinitiation at upstream open reading frames in amino acid-starved cells forms the basis for GCN4 translational control. - Abastado, J P (1991)
GCN4 encodes a transcriptional activator of amino acid-biosynthetic genes in Saccharomyces cerevisiae that is regulated at the translational level by upstream open reading frames (uORFs) in its mRNA leader. uORF4 (counting from the 5' end) is sufficient to repress GCN4 under nonstarvation conditions; uORF1 is required to overcome the inhibitory effect of uORF4 and stimulate GCN4 translation in amino acid-starved cells. Insertions of sequences with the potential to form secondary structure around uORF4 abolish derepression, indicating that ribosomes reach GCN4 by traversing uORF4 sequences rather than by binding internally to the GCN4 start site. By showing that wild-type regulation occurred even when uORF4 was elongated to overlap GCN4 by 130 nucleotides, we provide strong evidence that those ribosomes which translate GCN4 do so by ignoring the uORF4 AUG start codon. This conclusion is in accord with the fact that translation of a uORF4-lacZ fusion was lower in a derepressed gcd1 mutant than in a nonderepressible gcn2 strain. We also show that increasing the distance between uORF1 and uORF4 to the wild-type spacing that separates uORF1 from GCN4 specifically impaired the ability of uORF1 to derepress GCN4 translation. As expected, this alteration led to increased uORF4-lacZ translation in gcd1 cells. Our results suggest that under starvation conditions, a substantial fraction of ribosomes that translate uORF1 fail to reassemble the factors needed for reinitiation by the time they scan to uORF4, but become competent to reinitiate after scanning the additional sequences to GCN4. Under nonstarvation conditions, ribosomes would recover more rapidly from uORF1 translation, causing them all to reinitiate at uORF4 rather than at GCN4.